NEURAL NETWORK TECHNOLOGY FOR DETECTING ERRORS IN TEXT DOCUMENTS - Удовенко, Сергій; Затхей, Володимир; Тесленко, Олег (SWorldJournal, 2025)
The goal of this work is to develop a modified technology for error detection in text documents using a multilayer perceptron neural network. The proposed technology is implemented using an autoassociative neural network trained on a corpus of parallel te